Is the sinonasal questionnaire a useful screening instrument for chronic sinonasal diseases in pulmonary clinics?. (May 2013) - Ussavarungsi, Kamonpun; Limsuwat, Chok; Berdine, Gilbert; Nugent, Kenneth
Dixon and coworkers (Dixon AE, Sugar EA, Zinreich SJ, et al. Criteria to screen for chronic sinonasal disease. Chest 2009; 136: 1324–1332.) recently developed a five-item questionnaire for diagnosing chronic sinonasal disease in patients with asthma. Our study was designed to determine how frequently patients attending pulmonary clinics have chronic sinonasal disease and the relationship between questionnaire results and a history of sinus disease and current treatment for sinus disease. The participants were patients in pulmonary clinics at Texas Tech University Health Science Center, who answered the sinonasal questionnaire (SNQ). Additional information included a history of sinus disease or sinus/nasal surgery, smoking status, and current relevant medications. The participants included 28 men and 51 women. Patient ages ranged from 38 to 94 years (mean 62.2 years). Of all the patients, 28 patients (35.4%) had prior sinus disease, 10 (12.7%) had history of sinus or nasal surgery, 24 (30.4%) had history of asthma, and 10 (12.7%) were current smokers. Of them, 14 patients (17.7%) used nasal steroids, 12 (15.2%) used antihistamines, four (5.1%) used decongestants, nine (11.4%) used leukotriene inhibitors, 13 (16.5%) used oral corticosteroids, and two (2.5%) used combinations. The SNQ identified 39 patients (49.4%) as having chronic sinonasal diseases. Therefore, 14% of the participants had sinonasal symptoms but no prior diagnosis of sinus disease. Patients with prior sinus disease and nasal steroid use were more likely to have positive questionnaire result ( p < 0.001 and p < 0.032, respectively). The SNQ can identify patients with chronic sinonasal disease in pulmonary clinics. However, the significance of sinonasal disease and its treatment in these patients needs more study.